Poly(vinylpylrrolidone) as Surfactant in the Sol–Gel Preparation of Lithium Iron Phospate/Carbon Cathodes for Lithium‐Ion Batteries. Issue 8 (2nd June 2016) - Fan, Changling; Li, Qiyuan; Chen, Shilin; Fan, Jiwei; Wen, Zheng; Zeng, Taotao; Zhang, Xiang; Han, Shaochang
Abstract: Lithium iron phosphate/carbon (LiFePO4 /C) is synthesized by a modified sol–gel method, in which the nonionic surfactant poly(vinylpyrrolidone) (PVP) is used. PVP plays a dual roles in the preparation of LiFePO4 /C: it is used as surfactant to prevent the colloid particles and carbon source from aggregating, and is a carbon source. The carbon contents and conductivities of LiFePO4 /C increase with increasing of PVP. When the ratio of PVP to LiFePO4 reaches 1 ‰, the conductivity of LiFePO4 /C reaches its optimal value of 2.67×10 −2 S cm −1 and its discharge capacity at 1 C is 131.0 mAh g −1 . This is because the use of PVP leads particles that are small and have a homogeneous size distribution, which is due to dispersion by PVP. Titanium (Ti 4+ )‐doped samples, obtained from a sol–gel method, possess even better performances. The discharge capacities of this sample is 111.1 mAh g −1 at 5 C and 87.3 mAh g −1 at 8 C. The gap in potential between the oxidative and reductive peaks is as low as 0.2053 V, which shows its reversibility is excellent. Abstract : You down with PVP? Lithium iron phosphate (LiFePO4 ) is a promising cathode material for lithium‐ion batteries, but suffers from low conductivity and poor rate performance. Using surfactants in the sol–gel synthesis of LiFePO4 cathode materials increases conductivity by leading to smaller particle sizes, in turn increasing rate performance. Poly(vinylpyrrolidone) (PVP) proves an excellent nonionic surfactant for this purpose. For optimum performance, the amount of PVP should be neither too high nor too low.